A Research on Construction Industry - Technologies used for Construction Monitoring - Suresh, P. (Recent Research Reviews Journal, 2023)
The industrial sector of production and trade concerned with creating, restoring, updating, and maintaining infrastructure is known as the construction industry. Buildings and other constructed infrastructure, including roads, bridges, and other structures, are constructed by the construction industry. These sectors' offers will vary depending on the level of expertise, the emphasis on residential, industrial, and water constructions, etc. The study work from the construction business will briefly focus on construction monitoring utilising several technologies to monitor. This research work will describe construction monitoring, the technologies utilised at the site to monitor, and briefly explain one of the monitoring technologies which is used effectively in construction monitoring, their applications, and upcoming works.
Keywords: Construction Monitoring; IoT; Sensors; Technologies